Relationship between Professional Self-Efficacy and Psychological Well-Being of Judicial Assistants - Tylaitė, Svajunė; Barysė, Dovilė; Bareikytė, Simona (Teisė, 2024)
Judicial assistants have been gaining more and more legal expertise and practice in handling disputes. However, the professional role of judicial assistants has not been researched in Lithuania yet. The aim of the study is to investigate the relationship between the professional self-efficacy and psychological well-being of judicial assistants. Firstly, the conflicts in role of judicial assistants and work uncertainties have been identified. Secondly, the professional self-efficacy of judicial assistants is best predicted by satisfaction with interpersonal relationships and perceived value at work. In turn, perceived value at work is best predicted by satisfaction with interpersonal relationships, job satisfaction, and an increasing seniority. These results have been received after conducting a survey of 269 judicial assistants working in Lithuanian courts. The Additional Lithuanian Psychological Well-Being Scale (LPGS-P) was used to assess psychological well-being, whereas the short version of the Professional Self-Efficacy Scale (OCCSEFF) developed by Schyns and von Collani (2002) was employed to assess professional self-efficacy.